Business ratios and formulas : a comprehensive guide - Bragg, Steven M. (Hoboken, New Jersey : John Wiley & Sons, 2012)
'Business ratios, formulas, and statistics are used by controllers, business managers, and analyst to evaluate company operations and performance. This book presents a comprehensive resource of nearly 250 operational criteria, allowing managers to pick and choose the tools they need to best assess their organization's performance. The measurements contain not only financial matters but also those related to efficiency, effectiveness, capacity, and market share. In addition, measurements related to asset utilization, operating performance, cash flows, liquidity, capital structure, return on investment, and market performance.Each measurement includes a description, an explanation of the calculation, an example, and cautions regarding its use. There is also a description of an electronic spreadsheet to compile a standard set of measurements using Excel as the template.This new edition will include over 20 new measurements'--
Includes index.
Keywords: Business mathematics